Ideological Dimension in Bunga’ lalang : An Anthropological Linguistic Study - Magfirah Thayyib; Burhanuddin Arafah; Martin L. Manda; Fathu Rahman (Hasanuddin University, 2020)
This research aims to reveal the ideological dimension of bunga’ lalang tradition through the analysis of its two rituals namely mappammula ta’pa and mappammula mantanang. Bunga’ lalang is an agricultural tradition which exists in Luwu society, South Sulawesi, Indonesia. It refers to the series of rituals done by a bunga’ lalang (path opener) in every rice farming stage. This research employed descriptive qualitative method. The primary data were obtained through observation and interview while the secondary data were obtained through documentation. The data were analyzed using the combined/reviewed steps in ideological dimension analysis of social semiotics and dialectical ecolinguistics. There are several ideological dimensions in bunga’ lalang tradition through the analysis of two ritual discourses namely mappammula ta’pa and mappammula mantanang. The ideological dimensions revealed are classified into cognitive system, cultural assumption/belief, and mental/psychological system. All reflected the ideology of Luwu people/society in which bunga’ lalang tradition exists.